1997
DOI: 10.1046/j.1469-8137.1997.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine synthesis and accumulation in the hypersensitive response to TMV in Nicotiana tabacum

Abstract: SUMMARYThe possible involvement of polyamines in the tobacco mosaic virus (TMV)-induced hypersensitive reaction (HR) in Nicotiana tabacum (L.) cv. Samsun NN, which bears the N resistance gene, was investigated. Concentrations of free and conjugated polyamines, as well as the activities of their biosynthetic enzymes ornithine decarboxylase (ODC) and arginine decarboxylase (ADC), were analysed in the necrotic area (I, internal zone) and in the two concentric zones surrounding it (M, middle zone; E, external zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 26 publications
9
61
0
2
Order By: Relevance
“…First, synthesis of Spm is highly activated in necrotic tissue, yet the total amount of Spm decreases because consumption is enhanced. This possibility is supported by the finding that Put and Spd, precursors of Spm, are synthesized and highly accumulated around necrotic lesions on TMVinfected tobacco (Torrigiani et al, 1997). We in the present study and Scalet et al (1991) found that the amount of Put was significantly increased by mechanical wounding in both TMV-infected and mock-inoculated tobacco leaves and in wounded chickpea leaves, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…First, synthesis of Spm is highly activated in necrotic tissue, yet the total amount of Spm decreases because consumption is enhanced. This possibility is supported by the finding that Put and Spd, precursors of Spm, are synthesized and highly accumulated around necrotic lesions on TMVinfected tobacco (Torrigiani et al, 1997). We in the present study and Scalet et al (1991) found that the amount of Put was significantly increased by mechanical wounding in both TMV-infected and mock-inoculated tobacco leaves and in wounded chickpea leaves, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…In several higher plants, especially in the Solanaceae, polyamines have been shown to form mono-substituted and di-substituted basic amides with hydroxycinnamic acids (HCAs) ; these have been reported to be involved in the defence mechanism in several plant-pathogen interactions (Favali et al, 1997 ;Torrigiani et al, 1997 ;Walters & Mackintosh, 1997). The possibility now exists of manipulating polyamine metabolism in order to control plant diseases.…”
Section: mentioning
confidence: 99%
“…Less is known about susceptible (nn) tobacco plants in which TMV produces a systemic infection (Staskawicz et al, 1995). Torrigiani et al (1997) reported that in NN tobacco cv. Samsun, concentrations of free and conjugated polyamines increased towards the centre of the HR lesion ; maximum accumulation of free polyamines occurred 3 d after inoculation, whereas conjugates peaked 2 d later.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…NO também reage rapidamente com proteinas, especialmente amino ácidos reativos como cisteína e tirosina e com vários receptores e fatores de transcrição (STAMLER et al, 2001). NO pode induzir genes envolvidos na defesa e proteção da célula (FERRARINI et al, 2008 A planta, ao reconhecer um microrganismo invasor desencadeia uma resposta hipersensível, onde são liberadas EROs e NO, para delimitar a zona infectada e suprimir a multiplicação do patógeno (FLORES et al, 2008;HONG et al, 2008 A espermina é a poliamina biologicamente mais ativa que as demais, agindo na estabilização das membranas celulares, interagindo com proteínas nucleares, estimulando a síntese de pectina e de hemicelulose, além de exercer ação antioxidante (BOUCHEREAU et al, 1999) Alguns trabalhos mostram uma relação entre poliaminas e infecção da planta por patógenos, pois, nestas circunstâncias foi observado um aumento no nível de poliaminas, particularmente de espermina e espermidina (YAMAKAWA et al, 1998;TORRIGIANI et al, 1997). Não foi encontrado nenhum artigo que relacionasse a concentração de poliaminas em associações benéficas planta/bactéria.…”
Section: As Bactérias Endofíticas São Capazes De Modular a Fisiologiaunclassified